MECHANISMS IN ENDOCRINOLOGY: Estradiol as a male hormone. Issue 1 (July 2019) - Russell, Nicholas; Grossmann, Mathis
Abstract : Evidence has been accumulating that, in men, some of the biological actions traditionally attributed to testosterone acting via the androgen receptor may in fact be dependent on its aromatization to estradiol (E2). In men, E2 circulates at concentrations exceeding those of postmenopausal women, and estrogen receptors are expressed in many male reproductive and somatic tissues. Human studies contributing evidence for the role of E2 in men comprise rare case reports of men lacking aromatase or a functional estrogen receptor alpha, short-term experiments manipulating sex steroid milieu in healthy men, men with organic hypogonadism or men with prostate cancer treated with androgen deprivation therapy (ADT) and from observational studies in community-dwelling men. The collective evidence suggests that, in men, E2 is an important hormone for hypothalamic–pituitary–testicular axis regulation, reproductive function, growth hormone insulin-like growth factor-1 axis regulation, bone growth and maintenance of skeletal health, body composition and glucose metabolism and vasomotor stability. In other tissues, particularly brain, elucidation of the clinical relevance of E2 actions requires further research. From a clinical perspective, the current evidence supports the use of testosterone as the treatment of choice in male hypogonadism, rather than aromatase inhibitors (which raise testosterone and lower E2), selective androgen receptor modulators and selective estrogen receptor modulators (with insufficiently understood tissue-specific estrogenic effects). Finally, E2 treatment, either as add-back to conventional ADT or as sole mode of ADT could be a useful strategy for men with prostate cancer.